2014
DOI: 10.1016/j.tiv.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

An inter-machine comparison of tobacco smoke particle deposition in vitro from six independent smoke exposure systems

Abstract: There are several whole smoke exposure systems used to assess the biological and toxicological impact of tobacco smoke in vitro. One such system is the Vitrocell® VC 10 Smoking Robot and exposure module. Using quartz crystal microbalances (QCMs) installed into the module, we were able to assess tobacco smoke particle deposition in real-time. We compared regional deposition across the module positions and doses delivered by six VC 10s in four independent laboratories: two in the UK, one in Germany and one in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…The ratio difference in deposited nicotine concentration between cigarette and e-cigarette on the VC 10 ranged 7.65–10.03 at the first three dilutions but decreased to 2.52 at 1 l/min. These ratio comparisons show agreement at all dilutions on the RM20S; the VC 10 shows parity but there are greater product differences at higher air flow rates and we have previously reported variances in dose delivery from flow rates around 0.5 l/min [1]. …”
Section: Resultssupporting
confidence: 63%
“…The ratio difference in deposited nicotine concentration between cigarette and e-cigarette on the VC 10 ranged 7.65–10.03 at the first three dilutions but decreased to 2.52 at 1 l/min. These ratio comparisons show agreement at all dilutions on the RM20S; the VC 10 shows parity but there are greater product differences at higher air flow rates and we have previously reported variances in dose delivery from flow rates around 0.5 l/min [1]. …”
Section: Resultssupporting
confidence: 63%
“…A quartz crystal microbalance (QCM) (Vitrocell ® Systems, Waldkirch, Germany) was included in situ of exposure at position 4 within the Ames module, distal to the smoke inlet, as previously demonstrated [38][39][40]. QCMs provide a gravimetric measure of deposited mass, providing a valuable quality control (QC) measure of smoke exposure within and between runs, and allows data to be presented as a function of deposited mass (g/cm 2 ).…”
Section: Measuring Dosementioning
confidence: 99%
“…This way, different smoke generation and dilution systems can be characterized and compared directly regarding their performance and potential to supply suitable atmospheres for exposure studies. After three earlier studies (475,476,492) had convincingly demonstrated the value of quartz crystal microbalances (QCMs) for the quantitative assessment of cigarette smoke particle deposition, ADAMSON et al (493) used QCM technology for a comparative evaluation of Vitrocell ® smoke generation and exposure systems. The direct gravimetric measurement of precipitated mass per surface area in real time and in situ offered considerable advantages over traditional methods, such as measurement of fluorescence or differential mobility spectrometry backed by specific air flow rates.…”
Section: Air-liquid Interface (Ali) Exposure Systems: Vitrocell ®mentioning
confidence: 99%
“…When different concentrations of smoke were examined a linear correlation between optical density and dilution was shown. In the very same experiment, quartz crystal microbalances (QCMs) were installed into each of the seven pipe connectors between the smoke dilution elements and the base module -and not placed in any of the wells as done by ADAMSON et al (475,476,492,493) in a number of earlier studies. Particle deposition was monitored online and the final mass determined at the end of the smoking run.…”
Section: Air-liquid Interface (Ali) Exposure Systems: Vitrocell ®mentioning
confidence: 99%